The Mäanderhöhle. Analyses of palaeolithic cave art in Bavaria - Blumenröther, Julia; Bosinski, Gerhard; Gebelein, Dieter; Irlinger, Walter; Lenssen-Erz, Tilman; Maier, Andreas; Niggemann, Stefan; Pastoors, Andreas; Sommer, C. Sebastian; Steguweit, Leif; Uthmeier, Thorsten; Winterstein, Gerhard (Symbols in the landscape. Rock art and its context, 2015)
In 2011, the Mäanderhöhle in Franconia has become famous for supposedly housing the so far only evidence of Palaeolithic parietal art in caves in Germany. Lines on Cave Clouds (i.e. a special form of sinters) have been interpreted as representations of female figures of the Gönnersdorf type. Here, we present the result of a research campaign conducted between 2013 and 2014. Using photographical documentation, 3D-models of the lines, macroscopic and low power microscopic analysis, scratch experiments and iconographic comparisons, an anthropogenic origin of the lines can be exclude